2022
DOI: 10.47162/rjme.62.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, histopathological and immunohistochemical study of keratoacanthoma

Abstract: Keratoacanthoma (KA) is an epithelial tumor of the skin, classically considered as having a malignant transformation risk of 15%; however, many authors and the new World Health Organization (WHO) Classification of skin tumors consider KA as an incipient variant of the cutaneous squamous cell carcinoma (SCC). The aims of the study were to assess the clinical, histopathological (HP) and immunohistochemical (IHC) aspects of the KA and the role of these factors in malignancy occurrence. The studied group comprises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…The strong Pan-CK immunostaining (IRS score 9-12) contributes to the delineation of KA margins and assesses the integrity of the basement membrane [45]. In contrast to the moderate COX-2 expression of KAs in the lizards in this study (Figure 7A), strong COX-2 staining was observed in the KA with malignant transformation in panther chameleon 1, similar to what has been described in humans and bird SCCs, indicating increased cell proliferation, angiogenesis, and invasiveness [33,37,43,44,[46][47][48]. Based on these IHC results, COX-2 and E-cadherin staining especially can serve as an important tool in the diagnosis of KA and its differentiation from KA with malignant transformation and SCC in lizards.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The strong Pan-CK immunostaining (IRS score 9-12) contributes to the delineation of KA margins and assesses the integrity of the basement membrane [45]. In contrast to the moderate COX-2 expression of KAs in the lizards in this study (Figure 7A), strong COX-2 staining was observed in the KA with malignant transformation in panther chameleon 1, similar to what has been described in humans and bird SCCs, indicating increased cell proliferation, angiogenesis, and invasiveness [33,37,43,44,[46][47][48]. Based on these IHC results, COX-2 and E-cadherin staining especially can serve as an important tool in the diagnosis of KA and its differentiation from KA with malignant transformation and SCC in lizards.…”
Section: Discussionsupporting
confidence: 82%
“…Based on this variation, the World Health Organization (WHO) Classification of skin tumors proposed by the International Agency for Research on Cancer (IARC) categorizes different histologic variants of dermal SCC with acantholytic SCC, desmoplastic SCC and spindle cell SCC representing high-risk histologic variants, and verrucous SCC and KA representing low-risk histologic variants [8,30,31]. KA is defined as a well-differentiated, minimally invasive neoplasia with low metastatic potential [9,32,33]. In contrast to dogs and birds, KA in humans often shows a spontaneous regression phase that may occur within 4-6 months of the initial diagnosis [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keratoacanthoma* Keratoacanthoma is an epithelial tumor with clinical and histopathological features similar to SCC and a progression rate to malignancy of 15%, that has been classified into low-grade SCC in the recent WHO classification of cutaneous tumors (Murphy et al, 2018;Vîlcea et al, 2022).…”
Section: Malignant Skin Lesionsmentioning
confidence: 99%